(untitled) (Comparative & International Education Series, 2021)
This chapter is aimed at providing insights into main engagement and disengagement factors in international doctoral students (IDS) experiences at Russian universities. Following the Tinto’s model of student departure, we look at two domains of IDS integration - social and academic. Based on data from 20 semi-structured in-depth interviews with IDS in three Russian universities we show that involvement in the university knowledge community and monetary support are the main factors of engagement that leads to positive IDS experience. At the same time language barriers, bureaucracy of the system of Russian higher education and an absence of a peer-support from the national communities are named among the main disengagement factors.